2013
DOI: 10.1002/jocb.50
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Personality Traits and Environmental Predictors on Reproductive and Creative Imagination

Abstract: The purpose of this study was twofold: (1) to analyze the effects of both personality and environmental variables on the imagination of video/film major university students; and (2) to test the mediator effect resulting from the variable of social climate. The results of this study supported both indicators of imaginative capabilities and environmental influences. The hypothesis of the study—that the variable of social climate mediates the effects of personality/environmental predictors and both types of imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…The primary influence of openness on initiating imagination is a linear effect that agrees with recent research on the personality of creative designers (Kichuk & Wiesner, 1997;Liang et al, 2013). We observed that in addition to a limited range of scores near the negative pole of openness, a curvilinear effect, although minor, influences the initiating imagination.…”
Section: Effects Of Opennesssupporting
confidence: 90%
See 2 more Smart Citations
“…The primary influence of openness on initiating imagination is a linear effect that agrees with recent research on the personality of creative designers (Kichuk & Wiesner, 1997;Liang et al, 2013). We observed that in addition to a limited range of scores near the negative pole of openness, a curvilinear effect, although minor, influences the initiating imagination.…”
Section: Effects Of Opennesssupporting
confidence: 90%
“…Kichuk and Wiesner (1997) stated that successful designers are characterized by a high cognitive ability, which is closely associated with the openness trait. Liang et al (2013) studied media design majors and observed that openness reliably predicted creative and reproductive imaginations.…”
Section: Opennessmentioning
confidence: 99%
See 1 more Smart Citation
“…Other scholars assume a causal path lies between individual characteristics and social ties or creativity (e.g., Cho, Chung, Choi, Suh, & Seo, ; Liang, Chang, & Hsu, ; Shalley & Perry‐Smith, ). Thus, future research into alternative causal relationships using well‐designed panel data instead of cross‐sectional data may be called for.…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…Similarly, imagination on one hand constitutes a facilitator of linear thinking (reproductive imagination) and on the other hand, it is focused on mental processes within an inner world (creative imagination) (e.g. Liang, Chang & Hsu, 2014). Additionally, imaginative thinking supports flexibility in forming innovative solutions (Groves & Vance, 2014;Ogilvie, 1998).…”
Section: Edwards-schachter Et Al (2015)mentioning
confidence: 99%